GAYA HIDUP REMAJA DI SMA NEGERI 2 TAMBANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Desy Saputri; M. Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Humans are creatures who always have a variety of needs. As creatures who are never satisfied, they have a variety of ways to meet the needs and seek life satisfaction. So also in meeting modern lifestyle according to this present day, shopping, sightseeing, and follow the fashion trends and styles is one way to form a certain satisfaction for some people.Factor of needs high increasingly that make more and more progress in the field of information and communication technology. So many popping up stores that sell clothing needs and technology. As in various areas including Kampar.This study explains that students who have a certain lifestyle choices in terms of shopping, choice of clothing, trends and fashion and so on. And whether they tend to follow these things, and it's called lifestyle. Then also explain the factors that affect the lifestyle, either from internal or external factors.Keywords : Lifestyle; Hedonis; factors that influence the lifestyle